PEMBUATAN OTOMASI PENGATURAN KERETA API, PENGEREMAN, DAN PALANG PINTU PADA REL KERETA API MAINAN BERBASIS MIKROKONTROLER - Ari Beni Santoso; . Martinus; . Sugiyanto (Jurnal Ilmiah Teknik Mesin, 2013)
This research is intended to study experimentally the relationship between automation systemsfor the transportation system, while the emphasis is on the point of train control system on the rails.The design of manufacturing automation systems in this research using a microcontroller PUATTiny 2313-20 for setting the working mechanism of the dynamo on a train and ArduinoDuemilanove to open or close the railway doorstop. The data obtained from this research arespeed, braking system that is safe, and the optocoupler output. Safe braking distances used inresearch was 10 cm. Keywords : Automation Systems, Microcontroller, Optocoupler, Braking Systems.